The brokers of globalization: Towards a history of business associations in the international arena. Issue 2 (17th February 2023) - Eichenberger, Pierre; Rollings, Neil; Schaufelbuehl, Janick Marina
Abstract: This article is the introduction to the special issue looking at organised business in the international arena to gain better understanding of the role of this group of actors. The international strategies of national business interest associations and transnational business interest associations have largely been overlooked by business historians with a focus on multinational enterprise and global historians studying international organisations and international non-governmental organisations. The article explores in broad terms the historical development of these actors, their representation in the existing literature – historical as well as political and social scientific – before turning to some new research perspectives and the contributions of the articles in the special issue to this research agenda.